A dynamic study of cavity polaritons - Dunbar, L. A. (Trinity College (Dublin, Ireland). School of Physics, 2002)
Strong coupling between an atom and a cavity field is a well established phenomenon in the field of cavity quantum electrodynamics. However it was not until 1992 that improvements in growth technology resulted in the advent of strong coupling in semiconductor microcavities. The strong coupling in these novel systems is between a quantum well exciton and the confined photon field. Due to the similarities with three dimensional polaritons these states were called cavity polaritons. Due to their fast recombination rates cavity polaritons were anticipated in the early 1990s as a solution to the challenge of ultra-fast switching, which is needed in modern telecommunications. The recombination rate of the cavity polariton, being the average of the photon and exciton recombination rates, results in very fast recombination times. However, it was found that due to the peculiarities of the dispersion curve, these fast recombination rates were not realisable for non-resonantly (electronically) injected polaritons. The unusual dispersion curve that results from the admixture of an exciton photon system and its effect on scattering processes is one of the main topics of this thesis. The effect of the lower cavity polariton dispersion curve on the acoustic phonon broadening and polariton-polariton broadening is investigated using four wave mixing. A suppression of both of these scattering processes is detected on the lower polariton branch. Both suppressions, although from different mechanisms, are a result of the nature of the lower polariton dispersion curve. The suppression is shown to increase towards negative detunings, where the polariton is more photon-like. In the last three years stimulated emission of the cavity polariton has opened up new prospects for the strong coupling regime both in the commercial world and in the more fundamental aspects of research. For example, a new ‘inversionless’ polariton laser has recently been suggested which could be of commercial interest, and speculation as to whether a Bose-Einstein condensate can occur due to the bosonic nature of the polariton has resulted in much controversy in the research field. We endeavour to add to this knowledge by investigating the coherence time of the polariton with increased excitation. Longer coherence times are measured with an increased occupation, this is one of the signatures of a Bose Einstein condensate.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin